Integrasi Ekonomi Asia: Solusi Asia Menghadapi Krisis Global 2008 - Adrian Hidayat (The Winners, 2008)
No economies throughout the region managed to escape from the "global economic crisis in 2008" that was initiated in the United States. This is a logical consequence of the global economy that has been rolling along. The world economy is increasingly becoming more integrated and interdependent with one another. Exposure stems from the economic crisis in the prolonged United States subprime mortgage financial crisis, and eventually dragged the European economy, and also Asia. The Asian region was only affected, but even if only the impact of course, was enough to overwhelm the Asian region since the crisis has a major impact on a country's foreign exchange reserves. Therefore, after the G-20 summit held in Washington on November 15, 2008, the three major Asian countries, namely China, Japan and South Korea held a summit in Fukuoka Japanese initiative, which was attended by the three heads of government. This summit was to bring fresh air for the Asian region, because in addition to having a positive impact on Asian stocks, it also provides a new self confidence that Asia has formed an alliance that would at least fortify themselves (region) with the resulting stimulus policy. This initiative to find a solution is eventually expanded, and was welcomed by ASEAN countries, known as ASEAN Plus Three. Since in Asia there is already the East Asia Summit (East Asia Summit), the negotiations and the name of the group changed into the 6 partner countries of ASEAN. These six countries are Japan, China, South Korea, Australia, New Zealand, and India.